Alkali-silica reaction in geopolymer concrete - Lei, Jiawei (Nanyang Technological University, 2021)
The excavation of the Jurong Rock Cavern in Singapore produced rocks in a volume of about three million cubic meters. The excavated rocks potentially provide a valuable source for the local concrete aggregates, especially for Singapore, where the aggregates rely entirely on import. However, these rocks, mainly sedimentary siltstone and sandstone, were identified as alkali-silica reactive rocks, which would cause severer durability issues when they are used as aggregates in ordinary Portland cement (OPC) concrete. Geopolymer cement, a promising low-CO2 alternative binder to OPC, has been generally reported to be more resistant to ASR than the conventional OPC. The use of geopolymer concrete potentially provides a new solution to utilize the reactive aggregates. In addition, the local reactive rocks are rich in silica and alumina, two components which make them appealing for the geopolymer precursors. The objective of this study is therefore to produce a reliable ASR-free geopolymer concrete by using the local ASR-suspicious rocks as both aggregates and precursors. On one hand, the influence of the geopolymer pore solution on the ASR resistance of the geopolymer concrete was investigated to understand the reason for the ASR resistance of the geopolymer concrete. On the other hand, the method of geopolymer precursor synthesis by using the local ASR-suspicious rocks was explored. The results suggests the insufficient alkalinity and the deficiency of calcium in the geopolymer pore solution were the two controlling factors for the ASR resistance of the geopolymer concrete. The geopolymer precursor could be produced from the reactive rocks by the thermal treatment on a mix of rocks, alumina and sodium hydroxide in the powder form. The optimization of the binder was conducted by tailoring the composition of the precursor to improve the mechanical strength of the binder. Finally, an ASR-free geopolymer concrete was produced by using the local ASR-suspicious rocks as both aggregates and precursors.